Analisis produksi kelapa sawit kelompok tani di Desa Purwodadi Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Hanifah Rosa; Zulgani Zulgani; Etik Emiyati (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2020)
The purpose of this study is to determine the factors that influence the production of oil palm farmer groups in Purwodadi Village, Tebing Tinggi District, Tanjung Jabung Timur Regency. The data used in this study are primary data obtained utilizing field research sourced from oil palm farmers in Purwodadi Village, Tebing Tinggi District, Tanjung Jabung Barat Regency as samples. The sampling method used in this study is random sampling. The data were analyzed using descriptive and quantitative analysis methods, using multiple linear regression analysis tools. The results of the study found that the socio-economic characteristics of oil palm farmers in Purwodadi Village were based on gender, education level, work experience, number of workers, land area, capital, and coconut production. palm. The results of the data using multiple linear regression to calculate the oil palm production of farmer groups in Purwodadi Village which is influenced by the variable Capital with a coefficient of 0.420714, the variable of land area with a coefficient of 0.903379, and the variable of Labor with a coefficient of 0.255833 at the 95% confidence level has a positive effect and farmer groups in Purwodadi Village are significant for palm oil production if each variable is added. Keywords: Production, Charactiristics of oil palm farmers